Thunderclap headache syndrome presenting to the emergency department: an international multicentre observational cohort study. Issue 11 (10th February 2022) - Roberts, Tom; Horner, Daniel E; Chu, Kevin; Than, Martin; Kelly, Anne-Maree; Klim, Sharon; Kinnear, Frances; Keijzers, Gerben; Karamercan, Mehmet Akif; Wijeratne, Tissa; Kamona, Sinan; Kuan, Win Sen; et al.
Abstract : Background: Most headache presentations to emergency departments (ED) have benign causes; however, approximately 10% will have serious pathology. International guidelines recommend that patients describing the onset of headache as 'thunderclap' undergo neuroimaging and further investigation. The association of this feature with serious headache cause is unclear. The objective of this study was to determine if patients presenting with thunderclap headache are significantly more likely to have serious underlying pathology than patients with more gradual onset and to determine compliance with guidelines for investigation. Methods: This was a planned secondary analysis of an international, multicentre, observational study of adult ED patients presenting with a main complaint of headache. Data regarding demographics, investigation strategies and final ED diagnoses were collected. Thunderclap headache was defined as severe headache of immediate or almost immediate onset and peak intensity. Proportion of patients with serious pathology in thunderclap and non-thunderclap groups were compared by χ² test. Results: 644 of 4536 patients presented with thunderclap headache (14.2%). CT brain imaging and lumbar puncture were performed in 62.7% and 10.6% of cases, respectively. Among patients with thunderclap headache, serious pathology was identified in 10.9% (95%CI 8.7% to 13.5%) of cases—significantly higher than the proportion found in patients with a different headache onset (6.6% (95% CI 5.9% to 7.4%), p<0.001.). The incidence of subarachnoid haemorrhage (SAH) was 3.6% (95% CI 2.4% to 5.3%) in those with thunderclap headache vs 0.3% (95% CI 0.2% to 0.5%) in those without (p<0.001). All cases of SAH were diagnosed on CT imaging. Non-serious intracranial pathology was diagnosed in 87.7% of patients with thunderclap headache. Conclusions: Thunderclap headache presenting to the ED appears be associated with higher risk for serious intracranial pathology, including SAH, although most patients with this type of headache had a benign cause. Neuroimaging rates did not align with international guidelines, suggesting potential need for further work on standardisation.